Answer:
y = 0.3
Explanation:
Solve for y:
(3.2y - 1.8) - (5.2 y + 3.4) = -5.8
-(5.2y + 3.4) = -5.2y - 3.4:
3.2y - 1.8 -5.2y - 3.4 = -5.8
Grouping like terms, 3.2y - 1.8 - 5.2y - 3.4 = (3.2y - 5.2y) + (-1.8 - 3.4):
(3.2y - 5.2y) + (-1.8 - 3.4) = -5.8
3.2y - 5.2y = -2 y:
-2y + (-1.8 - 3.4) = -5.8
-1.8 - 3.4 = -5.2:
-5.2 - 2y = -5.8
Add 5.2` to both sides:
(5.2 - 5.2) - 2y = 5.2 - 5.8
5.2 - 5.2 = 0:
-2y = 5.2 - 5.8
5.2 - 5.8 = -0.6:
-2y = -0.6
Divide both sides of -2y = -0.6 by -2:
![\sf (-2)/(-2)y = (-0.6)/(-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/fovj0au2l94le7sdipllo0kxmiiz0ntmwk.png)
![\sf (-2)/(-2) = 1:](https://img.qammunity.org/2021/formulas/mathematics/high-school/se8zoscs578ig60du4wcr8eesu8pu8rdt5.png)
![\sf y = (-0.6)/(-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/irqcue0svv3vhrr0a95j6chrb1uv7fbgu7.png)
![\sf (-0.6)/(-2) = 0.3:](https://img.qammunity.org/2021/formulas/mathematics/high-school/albomzmblwnth01lwqusniaoz1ojfgwxr1.png)
y = 0.3